Effects of Dance Movement Therapy and Dance on Health-Related Psychological Outcomes. A Meta-Analysis Update - Koch, Sabine C.; Riege, Roxana F. F.; Tisborn, Katharina; Biondo, Jacelyn; Martin, Lily; Beelmann, Andreas (Frontiers in Psychology, 2019)
Background: Dance is an embodied activity, and when applied therapeutically can have several specific and unspecific health benefits. In this meta-analysis, we evaluated the effectiveness of dance movement therapy (DMT) and dance interventions for psychological health outcomes. Research in this area grew considerably from 1.3 detected studies/year in 1996-2012 to 6.8 detected studies/year in 2012-2018. Method: We synthesized 41 controlled intervention studies (N=2374; from 01/2012 to 03/2018), 21 from DMT, 20 from dance, investigating the outcome clusters of quality of life, clinical outcomes (with sub-analyses of depression and anxiety), interpersonal skills, cognitive skills, and (psycho-)motor skills. We included recent randomized controlled trials (RCTs) in areas such as depression, anxiety, schizophrenia, autism, elderly patients, oncology, neurology, chronic heart failure, and cardiovascular disease, including follow-up data in eight studies. Results: Analyses yielded a medium overall effect (d =.60), with high heterogeneity of results (I²=72.62%). Sorted by outcome clusters, the effects were medium to large (d=.53 to d=.85). All effects, except the one for (psycho-)motor skills, showed high inconsistency of results. Sensitivity analyses revealed that type of intervention (DMT or dance) was a significant moderator of results. In the DMT cluster, the overall medium effect was small, significant and homogenous/consistent (d=.30, p<.001, I²=3.47). In the dance intervention cluster, the overall medium effect was large, significant, yet heterogeneous/non-consistent (d=.81, p<.001, I²=77.96). Results suggest that DMT decreases depression and anxiety and increases quality of life, interpersonal, and cognitive skills, whereas dance interventions increase (psycho-)motor skills. Larger effect sizes resulted from observational measures, possibly indicating bias. Follow-up data showed that on 22 weeks after the intervention most effects remained stable or slightly increased. Discussion: Consistent effects of DMT coincide with findings from former meta-analyses. Most dance intervention studies came from preventive contexts, most DMT studies from institutional health-care contexts with more severely impaired clinical patients, where we found smaller effects, yet with higher clinical relevance. Methodological shortcomings of many included studies and heterogeneity of outcome measures limit results. Initial findings on long-term effects are promising.